High throughput phenotyping methods allowing breeding of Brachiaria and Panicum grasses for the ability of Biological Nitrification Inhibition - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Different phenotyping methods were developed and standardized to measure the phenomenon of Biological Nitrification Inhibition from a compregensive perspective (soil, roots, microbes) in tropical grasses, at first, the methods were developed for Brachiaria grasses but currently are being used for other pastures such as Panicum and legumes.